Extracellular vesicles released by steatotic hepatocytes alter adipocyte metabolism. Issue 2 (15th March 2022) - Mleczko, J.E.; Royo, F.; Samuelson, I.; Clos‐Garcia, M.; Williams, C.; Cabrera, D.; Azparren‐Angulo, M.; Gonzalez, E.; Garcia‐Vallicrosa, C.; Carobbio, S.; Rodriguez‐Cuenca, S.; Azkargorta, M.; et al.
Abstract: The composition of extracellular vesicles (EVs) is altered in many pathological conditions, and their molecular content provides essential information on features of parent cells and mechanisms of crosstalk between cells and organs. Metabolic Syndrome (MetS) is a cluster of clinical manifestations including obesity, insulin resistance, dyslipidemia and hypertension that increases the risk of cardiovascular disease and type 2 diabetes mellitus. Here, we investigated the crosstalk between liver and adipocytes by characterizing EVs secreted by primary hepatocytes isolated from Zucker rat model, and studied the effect they have on 3T3‐L1 adipocytes. We found that steatotic hepatocytes secrete EVs with significantly reduced exosomal markers in comparison with their lean counterpart. Moreover, proteomic analysis revealed that those EVs reflect the metabolic state of the parent cell in that the majority of proteins upregulated relate to fat metabolism, fatty acid synthesis, glycolysis, and pentose phosphate pathway. In addition, hepatocytes‐secreted EVs influenced lipolysis and insulin sensitivity in recipient 3T3‐L1 adipocytes. Untargeted metabolomic analysis detected alterations in different adipocyte metabolic pathways in cells treated with hepatic EVs. In summary, our work showed that steatosis has a significant impact in the amount and composition of EVs secreted by hepatocytes. Moreover, our data point to the involvement of hepatic‐EVs in the development of pathologies associated with MetS.